2021
DOI: 10.1111/jcmm.16924
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TUG1 attenuates ischaemia‐reperfusion‐induced apoptosis of renal tubular epithelial cells by sponging miR‐144‐3p via targeting Nrf2

Abstract: Renal ischaemia-reperfusion injury (IRI), as a common type of clinical acute kidney injury (AKI), causes injury to the kidney and can even result in acute renal failure (ARF). 1,2 Convincing evidence has revealed the molecular and pathological events in AKI. [3][4][5] Oxidative stress plays a vital role in renal IRI-induced cell apoptosis and is the result of the imbalance between oxidative and antioxidant systems. 6,7 The production of excessive ROS eventually cause membrane lipid peroxidation and oxidative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…In this study, we show that lncRNA-TUG1 is down-regulated in CKD, functions as miR-223-3p sponge by binding to its complementary site, and diminishes miR-223-3p-mediated Klotho suppression. Such sponge function of lncRNA-TUG1 is supported by earlier reports that several miRNAs including miR-145-5p 50 , miR-144-3p 53 , miR-29 58 can also bind to lncRNA-TUG1. The fact that lncRNA-TUG1 and miR-223-3p reciprocally antagonize each other underscores that they could form a double-negative feedback loop (Figure 8 k), which amplifies the capacity of miR-223-3p in suppressing Klotho expression.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In this study, we show that lncRNA-TUG1 is down-regulated in CKD, functions as miR-223-3p sponge by binding to its complementary site, and diminishes miR-223-3p-mediated Klotho suppression. Such sponge function of lncRNA-TUG1 is supported by earlier reports that several miRNAs including miR-145-5p 50 , miR-144-3p 53 , miR-29 58 can also bind to lncRNA-TUG1. The fact that lncRNA-TUG1 and miR-223-3p reciprocally antagonize each other underscores that they could form a double-negative feedback loop (Figure 8 k), which amplifies the capacity of miR-223-3p in suppressing Klotho expression.…”
Section: Discussionsupporting
confidence: 59%
“…Among them, lncRNA-TUG1 is known to be implicated in the pathogenesis of kidney diseases, although its function remains unclear and somewhat controversial. It has been reported that lncRNA-TUG1 exerts reno-protective effects by ameliorating fibrosis in diabetic nephropathy [49][50][51], attenuating ferroptosis [52] and apoptosis [53] of tubular epithelial cells in acute kidney injury, and enhancing mitochondrial function in podocytes [54]. However, lncRNA-TUG1 is also implicated in facilitating the development of CKD by inducing tubular epithelialmesenchymal transition [55,56], exacerbating inflammation and apoptosis of tubular cells [57].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the jury through binding with miR-144-3p. 33) Meanwhile, Peg 13 was inactivated in cerebral I/R injury and its overexpression protected against I/R-induced brain injury. 20) In this study, our results indicated that Peg13 was downregulated in MIRI.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic experiments clarified that miR-144-3p could target and inhibit Nrf2 expression. Furthermore, lncRNA TUG1 could promote Nrf2 expression by sponging miR-144-3p and improving oxidative stress damage and apoptosis of cells and tissues [129]. In summary, the lncRNA TUG1/ miR-144-3p/Nrf2 axis provides a new therapeutic approach for renal IRI.…”
Section: Renal Irimentioning
confidence: 96%